Risk factors and outcomes of myocardial injury after non-cardiac surgery in high-risk patients who underwent radical cystectomy. Issue 43 (23rd October 2020) - Yu, Jihion; Lim, Bumjin; Lee, Yongsoo; Park, Jun-Young; Hong, Bumsik; Hwang, Jai-Hyun; Kim, Young-Kug
Abstract : Abstract: Radical cystectomy is considered the standard treatment for patients with muscle-invasive bladder tumors and has high postoperative complication rates among urological surgeries. High-risk patients, defined as those ≥45 years of age with history of coronary artery disease, stroke, or peripheral artery disease or those ≥65 years of age, can have a higher incidence of cardiac complications. Therefore, we evaluated the incidence, risk factors, and outcomes of myocardial injury after non-cardiac surgery (MINS) in high-risk patients who underwent radical cystectomy. This retrospective observational study analyzed 248 high-risk patients who underwent radical cystectomy. MINS was defined as serum troponin I concentration ≥0.04 mg/L within postoperative 3 days. The risk factors for MINS were evaluated by multivariate logistic regression analysis. Postoperative outcomes were evaluated. The 1-year survival after radical cystectomy was also compared between patients who developed MINS (MINS group) and those who did not (non-MINS group) by Kaplan–Meier analysis. MINS occurred in 35 patients (14.1%). Multivariate logistic regression analysis showed that early diastolic transmitral filling velocity (E)/early diastolic septal mitral annular velocity (E') ratio (odds ratio = 1.102, 95% confidence interval [1.009–1.203], P = .031) and large volume blood transfusion (odds ratio = 2.745, 95% confidence interval [1.131–6.664], P = .026) were significantly associated with MINS in high-risk patients who underwent radical cystectomy. Major adverse cardiac events and 1-year mortality were significantly higher in the MINS group than in the non-MINS group (17.1% vs 6.1%, P = .035; 28.6% vs 12.7%, P = .021, respectively). Kaplan–Meier analysis showed significantly lower 1-year survival in the MINS group than in the non-MINS group ( P = .010). MINS occurred in 14.1% of patients. High E/E' ratio and large volume blood transfusion were risk factors for MINS in high-risk patients who underwent radical cystectomy. Postoperative major adverse cardiac events and 1-year mortality were significantly higher in the MINS group than in the non-MINS group. Preoperative evaluation of risk factors for MINS may provide useful information to detect cardiovascular complications after radical cystectomy in high-risk patients.